Optimizing Medical Image Security Using Combined DWT-DCT-SVD Watermarking and RLE Compression Strategies - Mahiruna, Adiyah; Ngatimin, Ngatimin; Aulia, Lathifatul; Oleiwi, Ahmed Kareem; Rachmawanto, Eko Hari (Journal of Intelligent Computing & Health Informatics, 2024)
Medical images, including MRI, CT, ultrasound, X-rays, and ECG, are crucial for diagnostics; however, they present significant data security challenges. This study introduces a novel watermarking technique that utilizes discrete wavelet transform (DWT), discrete cosine transform (DCT), and singular value decomposition (SVD) to enhance the security, confidentiality, and integrity of medical images. In addition, Run Length Encoding (RLE) is implemented for efficient compression, which significantly reduces data memory requirements. The proposed method demonstrated a notable improvement in the peak signal-to-Noise Ratio (PSNR), increasing by up to 5 dB compared to existing techniques, and achieved a file size reduction of 15-30%. These advances ensure that high-quality images consume less storage space while maintaining diagnostic integrity. The improved PSNR values indicate that the watermark remains imperceptible, making the proposed method highly effective for clinical applications. Compared to existing methods, the proposed method offers enhanced robustness against digital attacks and better image quality preservation. These findings support the secure and efficient handling of medical image data, thereby promoting their use in clinical environments.